2020
DOI: 10.1101/2020.01.13.904979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heterosis of leaf and rhizosphere microbiomes in field-grown maize

Abstract: Word count (Total): 6693 Word count (Introduction): 818 Word count (Methods): 3241 Word count (Results): 1859 Word count (Discussion): 783 Number of figures: 6 (all in color) Number of tables: 1 Supporting Information: 4 tables + 7 figures (all in color) Word count (Acknowledgements): 105 Summary:• Macroorganisms' genotypes shape their phenotypes, which in turn shape the habitat available to potential microbial symbionts. This influence of host genotype on microbiome composition has been demonstrated in many s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 83 publications
2
34
1
Order By: Relevance
“…The host plant is Arabidopsis thaliana, unless otherwise stated. Less is known about fungi and oomycetes, although there have been studies profiling the fungal or oomycete communities in the phyllosphere of different plant species (e.g., Arabidopsis, rice, maize, and tropical mangrove) (Horton et al, 2014;Agler et al, 2016;Yao et al, 2019;Wagner et al, 2020). Studies using fluorescence-based approaches have also demonstrated the diversity and spatial distribution patterns of different bacterial taxa on the leaf surface of Arabidopsis and bean plants (Remus-Emsermann et al, 2014;Esser et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The host plant is Arabidopsis thaliana, unless otherwise stated. Less is known about fungi and oomycetes, although there have been studies profiling the fungal or oomycete communities in the phyllosphere of different plant species (e.g., Arabidopsis, rice, maize, and tropical mangrove) (Horton et al, 2014;Agler et al, 2016;Yao et al, 2019;Wagner et al, 2020). Studies using fluorescence-based approaches have also demonstrated the diversity and spatial distribution patterns of different bacterial taxa on the leaf surface of Arabidopsis and bean plants (Remus-Emsermann et al, 2014;Esser et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies in different plant species, including Arabidopsis , grapevine, and the perennial mustard plant Boechera stricta , have shown that the leaf and root microbiotas can overlap substantially in key community members, although the overall community structure and composition can differ (Bai et al, 2015; Zarraonaindia et al, 2015; Wagner et al, 2016). These studies suggest that the leaf and root microbiotas may be derived from a similar source (i.e., soil) and/or that the two communities may interact with each other in natural environments (e.g., through wind, rain splashing, or insect movement) (Vogel et al, 2016; Tkacz et al, 2020; Liu et al, 2020a). The soil origin of the phyllosphere microbiota is supported by reports showing that both root and leaf microbiotas depend on the soil community (Zarraonaindia et al, 2015; Finkel et al, 2019) and that some endophytic rhizobia bacteria inoculated in soil can migrate to rice leaves through vascular tissue (Chi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to previous work in the rhizosphere microbiome (Carrión et al 2019; H. Liu et al 2021), transplanting microbial communities from stressful conditions onto plants in the growth chamber did not improve disease resistance, so we cannot conclude whether stress-induced compositional shifts in phyllosphere microbiota are adaptive for the host plant. While it is always possible that other, unmeasured traits were improved by microbiome transplant, our results may reflect growing evidence that host selection is weaker in the phyllosphere than the rhizosphere (Wagner et al 2020).…”
Section: Discussionmentioning
confidence: 80%